Double Strike Approach for Tumor Attack: Engineering T Cells Using a CD40L:CD28 Chimeric Co-Stimulatory Switch Protein for Enhanced Tumor Targeting in Adoptive Cell Therapy - Olguín-Contreras, Luis Felipe; Mendler, Anna N.; Popowicz, Grzegorz; Hu, Bin; Noessner, Elfriede (Frontiers in Immunology, 2021)
Activation of co-stimulatory pathways in cytotoxic T lymphocytes expressing chimeric antigen receptors (CARs) have proven to boost effector activity, tumor rejection and long-term T cell persistence. When using antigen-specific T cell receptors (TCR) instead of CARs, the lack of co-stimulatory signals hampers robust antitumoral response, hence limiting clinical efficacy. In solid tumors, tumor stroma poses an additional hurdle through hindrance of infiltration and active inhibition. Our project aims at generating chimeric co-stimulatory switch proteins (CSP) consisting of intracellular co-stimulatory domains (ICD) fused to extracellular protein domains (ECD) for which ligands are expressed in solid tumors. The ECD of CD40L was selected for combination with the ICD from the CD28 protein. With this approach, it was expected to not only provide co-stimulation and strengthen the TCR signaling, but also, through the CD40L ECD, facilitate the activation of tumor-resident antigen-presenting cells (APCs), target tumor endothelium and induce TCR-MHC independent apoptotic effect on tumor cells. Since CD28 and CD40L belong to different classes of transmembrane proteins (type I and type II, respectively), creating a chimeric protein presented a structural and functional challenge. We present solutions to this challenge describing different CSP formats that were successfully expressed in human T cells along with an antigen-specific TCR. The level of surface expression of the CSPs depended on their distinct design and the state of T cell activation. In particular, CSPs were upregulated by TCR stimulation and downregulated following interaction with CD40 on target cells. Ligation of the CSP in the context of TCR-stimulation modulated intracellular signaling cascades and led to improved TCR-induced cytokine secretion and cytotoxicity. Moreover, the CD40L ECD exhibited activity as evidenced by effective maturation and activation of B cells and DCs. CD40L:CD28 CSPs are a new type of switch proteins designed to exert dual beneficial antitumor effect by acting directly on the gene-modified T cells and simultaneously on tumor cells and tumor-supporting cells of the TME. The observed effects suggest that they constitute a promising tool to be included in the engineering process of T cells to endow them with complementary features for improved performance in the tumor milieu.